Comparison Investigation of Thermal Performance of Shell and Tube Heat Exchanger with Helical Baffles - Mohd Zamri, Muhammad Haziq; Hassan, Nurhafizzah (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study was a comparison investigation of the influence of helical baffles on the thermal performance of heat in shell and tube heat exchangers, utilizing the SolidWorks 2023 software. A 3D model was generated and computational fluid dynamics (CFD) simulations were conducted to compare the heat transfer rates between single segment and helical baffles using the Logarithmic Mean Temperature Difference (LMTD) method. Water and olive oil were used as hot fluids while water was used as the cold fluid. The findings showed significant improvement with the implementation of helical baffles. The water and water simulations indicated a result on the heat transfer rate (Q) for single segment baffles, 623.435 kW and helical baffles, 676.663 kW. Helical baffles improve the mixing of fluids and increase turbulence which in turn enhanced heat transfer. Conversely, olive oil and water simulation gained a lower heat transfer rate. The study emphasizes the need to select optimal baffles and consider fluid properties to achieve maximum performance in heat exchangers. Heat transfer rates were additionally influenced by other factors such as temperature, pressure and tube properties.